Le projet « Pour des choix gagnants, aiguisons nos réflexes » - Relais-femmes (2022)
Une série de quatre capsules-vidéo met en lumière les retombées d'accompagnements..Cette deuxième vidéo présente les retombées du projet « Pour des choix gagnants, aiguisons nos réflexes », et a été réalisée par le centre de femmes Entr'elles de Granby ainsi que le comité contre l'appauvrissement des femmes. Elle met en valeur l'importance de «faire de la sensibilisation et de l'éducation populaire pour parler des facteurs de l'appauvrissement des femmes; et de distinguer la sécurité économique de l'autonomie économique des femmes» a souligné Véronique Latulippe, animatrice au centre de femmes Entr'elles de Granby et chargée de projet au comité contre l'appauvrissement des femmes.
Keywords: amériques; approches et analyses; discipline; femmes*; inégalités; pauvreté; québec; relais-femmes; ressource en ligne; régions géographiques; sciences de la gestion; systèmes d'oppressions; économie

Gendered paths to asset accumulation? Markets, savings, and credit in developing countries - Catanzarite, Zachary; Diana, Carmen Diana; Doss, Cheryl D.; Oduro, Abena D.; Suchitra, J. Y.; Swaminathan, Hema (Feminist Economics, 2019)
An extensive literature shows how property inheritance is biased against women in many developing countries, yet relatively little attention has been given to gender bias in other means of acquiring physical assets, such as the market. Using individual-level data from Ecuador, Ghana, and Karnataka, India, this study analyzes modes of acquisition and financing of housing, agricultural land, other real estate, and businesses. The findings show that women acquire fewer of their assets through the market than men, and that in asset markets, both men and women are more likely to use their own savings than to use credit. The study also analyzes current loans for asset acquisition and finds that, in general, women tend to be somewhat disadvantaged in securing formal bank loans. The results suggest that financial inclusion to promote more gender equal access to accumulation of assets should focus on both savings and credit, with priority to savings.
Keywords: OFDIG; afrique; amériques; approches et analyses; asie; discipline; femmes*; inégalités; microcrédit; ressource en ligne; régions géographiques; sciences de la gestion; systèmes d'oppressions; économie